How do we best support adolescents with low academic performance and learning disabilities in the era of pandemic learning loss? The importance of intensive learning strategy interventions - O’Brien, Chris; Boudah, Daniel J.; Lopuch, Jeremy; Nance, Aaron (Frontiers in Education, 2023)
The COVID-19 pandemic put a spotlight on learning loss that teachers of low-performing adolescents, including those with learning disabilities (LD), have confronted for decades. Federal funding offers opportunities for school districts across the country to implement evidence-based interventions that promote outcomes for students with learning difficulties in middle and high schools including those from culturally and linguistically diverse backgrounds. There is a risk, however, of funding weak models of tutoring that prioritize subject-specific "homework help" in contrast to more effective programs. Research directs schools to the use of coherent intervention programs which are built into the school day, integrated into IEPs, facilitated by competent educators, employ a model of explicit-intensive instruction that has the most significant impact on learning outcomes for students with learning difficulties, and prioritize strategies that generalize to multiple content areas. Recommendations are presented for developing Individualized Education Programs for adolescents with LD, which align with the need for challenging, ambitious goals and special education services that are based on an extensive body of research.Disabilities in The Era of Pandemic Learning Loss?The Importance of Intensive Learning Strategy Interventions.COVID-19 created a crisis in education and resulted in significant losses in instructional time in the classroom. Despite attempts by educators to maintain their instructional hours and provide quality educational opportunities to maintain educational growth, the full impact of lost classroom instructional time is being realized in lower reading outcomes and significant